Metadynamic recrystallization behavior of β-solidified TiAl alloy during post-annealing after hot deformation. (February 2020) - Tang, Bin; Wang, William Yi; Xiang, Lin; Liu, Yan; Zhu, Lei; Ji, Shengli; He, Jian; Li, Jinshan
Abstract: The metadynamic recrystallization (MDRX) of β-solidified TiAl alloy and its effects on microstructural homogeneity were investigated in the present work. Based on the comprehensive microstructure characterizations in terms of scanning electron microscope in back-scattered electron (BSE) mode and electron back scattered diffraction (EBSD) technique, it is found that the occurrence of MDRX during the post-annealing process after hot compression leads to the decomposition of lamellar colonies, grain equalization and reduction of geometrically necessary dislocation. The MDRX in present alloy during interpass annealing process has a hardening effect on the subsequent flow behavior, while it is restricted due to the phase transformation γ to α when annealing at 1200 °C. Moreover, the occurrence of MDRX can reduce the microstructure heterogeneity among various areas induced by the different strains and stain rates, thus, to result in the microstructural homogenization. Through investigating the MDRX behavior, the present work supports important information for optimizing forged microstructure of TiAl alloys. Graphical abstract: Image 1 Highlights: The MDRX in TNM alloy has a hardening effect on the subsequent flow behavior. The MDRX can lead to the decomposition of lamellar colonies, grain equalization and reduction of GND. The α2 .→ β/B2 transformation occurs in the lamellar colony during the post-annealing process. The MDRX can reduce the microstructure difference between different areas.